2020
DOI: 10.21037/jtd-20-2953
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and mid-term effects of radiofrequency ablation in mitral valve surgery in patients with different left atrial sizes

Abstract: Background: To evaluate the efficacy of atrial fibrillation radiofrequency ablation (AFRA) in patients with chronic valvular atrial fibrillation (AF) with different left atrial sizes [left atrial diameter (LAD) >45 or ≤45 mm].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…As discussed earlier, this bias might be due to the variation in surgical methodology. Mitral valve surgery was safe and effective in patients in restoring SR by using ablation to treat AF [24–26] . There is no doubt that surgical ablation can successfully block AF conduction to maintain the normal SR, as reported in previous reviews.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…As discussed earlier, this bias might be due to the variation in surgical methodology. Mitral valve surgery was safe and effective in patients in restoring SR by using ablation to treat AF [24–26] . There is no doubt that surgical ablation can successfully block AF conduction to maintain the normal SR, as reported in previous reviews.…”
Section: Discussionsupporting
confidence: 54%
“…Mitral valve surgery was safe and effective in patients in restoring SR by using ablation to treat AF. [ 24 26 ] There is no doubt that surgical ablation can successfully block AF conduction to maintain the normal SR, as reported in previous reviews. Phan et al [ 27 ] and McClure et al [ 6 ] evaluated the efficacy of promoting SR in patients who underwent cardiac surgery combined with surgical ablation.…”
Section: Discussionmentioning
confidence: 76%
“…Female patients with a LAD ≥47 mm and male patients with a LAD ≥53 mm are considered to be severely enlarged ( 11 ), and thus, a LAD >50 mm is considered severe enlargement. Our previous report ( 12 ) showed that conventional thoracotomy combined with surgical ablation of AF for LAD <45 mm provides good results. Also, the early postoperative and 2-year AF conversion rates can be as high as 91% and 84% respectively, which were 84% and 70% respectively for LAD >45 mm, and these differences were statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation is the most common sustained arrhythmia that increases with age and presents with a wide spectrum of symptoms and severity, including reentry theory and focal agitation [17,18]. Despite shorter ablation times, faster balloon cooling, and longer thawing times, ablation of atrial fibrillation with a second-generation cryoballoon is associated with higher success rates of pulmonary venous dissociation, acute and long-term PV isolation rates are high, AE rates are similar, and atrial fibrillation is absent [19].…”
Section: Discussionmentioning
confidence: 99%